Implications of off-label use: An example from the final results of an observational cohort study on Intrinsa® (testosterone patch). (June 2014) - Osborne, Vicki; Layton, Deborah; Shakir, Saad AW
Introduction: Off-label use is where a medicinal product is used for a medical purpose not in accordance with the authorised product information. Intrinsa® is a transdermal testosterone patch, which is indicated for use in hypoactive sexual desire disorder in bilaterally oophorectomised and hysterectomised women receiving concomitant estrogen therapy. Objectives: To describe the utilization characteristics of patients prescribed testosterone patch (Intrinsa®) and to assess, where possible, if the product is being used according to the authorised product information. Study design: Patients identified from dispensed prescriptions issued by general practitioners for Intrinsa® between March 2007 and August 2010. Postal questionnaires were sent to general practitioners six months following the date of the first prescription for Intrinsa® for each patient, requesting information including patient demographics and drug utilization. Main outcome measures: Menopausal status and use of concomitant estrogen therapy. Results: The final cohort consisted of 3073 patients; the majority were females (3017, 98.2%). The most commonly reported indication was hypoactive sexual desire disorder in 2324 female patients (77.0%). Only 43.5% female patients ( n = 1313) were reported to have been hysterectomised and bilaterally oophorectomised. For 1029 (34.1%) female patients there was no evidence that the patient was using concomitant estrogen therapy. Overall, only 643 patients (20.9%) in the cohort were being prescribed Intrinsa® according to the manufacturer's recommendations. Conclusions: Evidence obtained solely from clinical trials might not be generalisable where off-label prescribing occurs in real-life, so evidence from post-marketing observational studies is important to provide complimentary data on a product's safety and effectiveness.